2014
DOI: 10.1039/c4md00089g
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitors of the human neuraminidase enzymes

Abstract: A review of known small molecule inhibitors and substrates of the human neuraminidase enzymes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
64
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(65 citation statements)
references
References 100 publications
(181 reference statements)
1
64
0
Order By: Relevance
“…Current treatments for influenza include inhaled zanamivir (Relenza), oral oseltamivir (Tamiflu) and intravenous peramivir (Rapivab), which were developed as substrate analogs targeting viral NA (von Itzstein et al 1993 ; Lagoja and De Clercq 2008 ; Cairo 2014 ). Previous studies have shown that NA-VLP purified using sucrose gradient centrifugation exhibit enzymatic activity (Mohan et al 2010 ; Garcia et al 2014 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Current treatments for influenza include inhaled zanamivir (Relenza), oral oseltamivir (Tamiflu) and intravenous peramivir (Rapivab), which were developed as substrate analogs targeting viral NA (von Itzstein et al 1993 ; Lagoja and De Clercq 2008 ; Cairo 2014 ). Previous studies have shown that NA-VLP purified using sucrose gradient centrifugation exhibit enzymatic activity (Mohan et al 2010 ; Garcia et al 2014 ).…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Fig. 6 a, product is uniquely formed in the presence of NA-VLP and the enzyme activity is reversed by the addition of the inhibitor DANA (Neu5Ac2en), a transition state analog and the parent compound of FDA-approved NA inhibitors (von Itzstein et al 1993 ; Lagoja and De Clercq 2008 ; Cairo 2014 ). Importantly, control measurements using VLP prepared in the absence of NA expression (native-VLP), in which p24 levels were used to normalize the amount of VLP in the samples, exhibited no activity (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The acrosome appears to contain a further reservoir of sialidases, which are released physiologically during the acrosome reaction prior to fertilization (8,12). Because NEU1 and NEU3 together are able to desialylate several different glycoconjugates (␣2,3-, ␣2,6-, and ␣2,8-sialylated), a significant restructuring of the glycocalyx can be expected (13)(14)(15).…”
mentioning
confidence: 99%